Website-Based Student Payment System with Payment Gateway at Hasbullah Bahrul Ulum Islamic Boarding Schoo - Handy, Arya Dhiva; Munawarah, Munawarah (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Technological advances allow humans to more easily carry out their activities, and one way technology is utilized is by assisting in payment transactions. This research presents the stages in developing a web-based payment system with a payment gateway at the Hasbullah Bahrul Ulum Islamic Boarding School which will later function to facilitate the payment process with a payment gateway system, make it easier for students or guardians of students to check their sharia bills and also minimize recording errors so that they can Process financial records appropriately. The aim of this research is to meet needs and facilitate the process of checking bills and payments at the Hasbullah Bahrul Ulum Islamic Boarding School. This system is designed using the PHP programming language and MySQL for the database. This program package is designed to simplify the development of this system, allowing it to be used to create web page displays, and build payment system applications. This is in accordance with the needs desired by Islamic boarding school administrators, such as managing student data, number of students, bills, number of daily transactions, and creating reports to see bill summaries